1983
DOI: 10.1104/pp.73.3.598
|View full text |Cite
|
Sign up to set email alerts
|

Auxin-Induced Ethylene Production as Related to Auxin Metabolism in Leaf Discs of Tobacco and Sugar Beet

Abstract: ABSTRACIExogenously supplied indole-3-acetic acid (IAA) stimulated ethylene production in tobacco (Nicotiana glauca) leaf discs but not in those of sugar beet (Beta vulgaris L.). The stimulatory effect of IAA in tobacco was relatively small during the first 24 hours of incubation but became greater during the next 24 hours. It was found that leaf discs of these two species metabolized I1-'4CIIAA quite differently. The rate of decarboxylation in sugar beet discs was much higher than in tobacco. The latter conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…It may be emphasized from the physiological point of view that in the presence of oxygen the peroxidase-IAA system yields strong oxidizing species. Since it has been reported that the fornation of ethylene (plant hornone) is promoted by the addition of IAA (137)(138)(139)(140)(141), there is a possibility that the ethylene formation is promoted by such oxidizing species.…”
Section: Metabolismmentioning
confidence: 99%
“…It may be emphasized from the physiological point of view that in the presence of oxygen the peroxidase-IAA system yields strong oxidizing species. Since it has been reported that the fornation of ethylene (plant hornone) is promoted by the addition of IAA (137)(138)(139)(140)(141), there is a possibility that the ethylene formation is promoted by such oxidizing species.…”
Section: Metabolismmentioning
confidence: 99%
“…Recent studies of auxin metabolism in tobacco leaves (4,18) have suggested that the rate of ethylene production in the IAAtreated tissue is dependent on the formation of IAA conjugates and their ability to release free IAA (15). In this respect, it was reported that the synthetic IAA conjugate, IAA la, which can induce ethylene production in vegetative tissues (15,16), was much more active when applied with sucrose (3).…”
mentioning
confidence: 99%
“…Although the findings reported herein and elsewhere (3,4,18) suggest IAA mediation in the sucrose-stimulated ethylene production, other mechanisms to account for the effect of sugars should also be taken into consideration (19). …”
mentioning
confidence: 99%
See 2 more Smart Citations